Acetate and Lactate Production During Two-Stage Anaerobic Digestion of Food Waste Driven by Lactobacillus and Aeriscardovia - Moestedt, Jan; Müller, Bettina; Nagavara Nagaraj, Yashaswini; Schnürer, Anna (Frontiers in Energy Research, 2020)
Background: In a previous study, single-stage processes were compared with two-stage processes, using either food waste alone or mixed with thin stillage as substrate. Overall methane yield increased (by 12%) in two-stage compared with single-stage digestion when using food waste, but decreased when food waste was co-digested with thin stillage (50:50 on VS basis). The obtained difference in methane yield was likely caused by a higher acetate level in the first stage reactor operating with food waste alone (around 20 g/L) compared to the reactor also treating thin stillage (around 8 g /L). The present study sought to shed additional light on possible causes of the large difference in methane yield by scrutinizing the microbial community in the first- and second-stage reactors, using a combined Illumina sequencing and qPCR approach. Results: In the first-stage process, acid-tolerant Aeriscardovia and Lactobacillus formed a highly efficient consortium. For food waste with high levels of acetate (20 g/L, equal to 0.14 g acetate/g VS) was produced but when thin stillage was added the pH was lower (<4), resulting in lactate production exceeding acetate production. This difference in hydrolysate composition between the reactors resulted in development of slightly different communities in the second-stage, for both hydrolysis, fermentation, and acetogenesis. High acetate concentration appeared to promote proliferation of different syntrophic consortia, such as various syntrophic acetate oxidizers, members of the genus Syntrophomonas and candidate phylum Cloacimonetes, likely explaining the higher methane yields with two-step compared with single-stage digestion of food waste. Conclusion: Using food waste as sole substrate resulted in enrichment of Lactobacillus and Aeriscardovia and high acetate yields in the first-stage reactor. This was beneficial for biogas yield in two-stage digestion, where efficient acid-degrading syntrophic consortia developed. Addition of thin stillage contributed to low pH and higher lactate production, which resulted in decreased methane yield in the two-stage process compared with using food waste as sole substrate.